The experience of students in the South African-Cuban medical training program : an encounter with medical pluralism - Lungelow, Danielle (Department of Commercial Law, 2015)
The Cuban Medical Training program is an initiative that provides bursaries to international students from disadvantaged backgrounds. Understanding the experiences of South African participants, particularly those who complete their transitional component at University of Cape Town (UCT), and how they are prepared to meet the aims of the South African-Cuban Medical Training Program (SACMTP), the needs of their local communities, and ultimately, the needs of the South African health system, is the focus of my research.